UKŁAD POKOJOWY WŁADYSŁAWA HERMANA Z BRZETYSŁAWEM II W 1093(94) ROKU W ŚWIETLE KRONIKI KOSMASA - Benyskiewicz, Krzysztof (In Gremium. Studies in History, Culture and Politics, 2008)
THE ACCOUNT OF THE PEACE TREATY OF 1093(94) BETWEEN WŁADYSŁAW HERMAN AND BRETISLAUS II IN KOSMAS’S BOHEMIAN CHRONICLE S u m m a r y The Bohemian Chronicle by Kosmas and the Polish Chronicle by Gallus Anonimus are the two sources which give an account of the Polish-Czech relations in 090. At that time, a conflict broke out between duke Władysław I Herman of Poland and duke Bretislaus II of Bohemia: Poland held back the usual tribute from Silesia that was to be paid to the Kingdom of Bohemia. In retribution, the Bohemian ruler first ravaged Silesia and then gave his support to Herman’s firstborn son, Zbigniew, who, though banned from the country, laid claim to the throne. Thus Zbigniew, with his supporters and assisted by Bretislaus, took control over Wrocław and so family strife began between two Piasts: Władysław and Zbigniew. The ensuing hostilities did not produce a definitive solution to the conflict and a peace treaty was signed, under which Zbigniew was to rule the Silesian province as his father’s vassal. Here the two Chronicles differ from each other. According to Kosmas, it was a trilateral agreement entered by Bretislaus II, Władysław I Herman, and Bolesław III Krzywousty /’Wrymouth’/. Gallus Anonimus’s account only has Władysław I and Zbigniew compose their differences over Silesia, with Bretislaus appearing as the Polish ruler’s ally in the last phase of the dispute. The discrepancy suggests a flaw in Kosmas’s account which, in its description of the negotiations of 096, mentions Bolesław III, totally ignoring Zbigniew. But it was the latter who fought in Silesia and who was likely to have made peace with the Premyslid and the old Piast. The treaty concerned the whole of Silesia, from which Zbigniew paid a vassal tribute to Bretislaus.